Physiology and Pathology of Calcium Signaling in the Brain - Kawamoto, Elisa M.; Vivar, Carmen; Camandola, Simonetta (Frontiers in Pharmacology, 2012)
Calcium (Ca2+) plays fundamental and diversified roles in neuronal plasticity. As second messenger of many signaling pathways, Ca2+ as been shown to regulate neuronal gene expression, energy production, membrane excitability, synaptogenesis, synaptic transmission, and other processes underlying learning and memory and cell survival. The flexibility of Ca2+ signaling is achieved by modifying cytosolic Ca2+ concentrations via regulated opening of plasmamembrane and subcellular Ca2+ sensitive channels. The spatiotemporal patterns of intracellular Ca2+ signals, and the ultimate cellular biological outcome, are also dependent upon termination mechanism, such as Ca2+ buffering, extracellular extrusion, and intra-organelle sequestration. Because of the central role played by Ca2+ in neuronal physiology, it is not surprising that even modest impairments of Ca2+ homeostasis result in profound functional alterations. Despite their heterogeneous etiology neurodegenerative disorders, as well as the healthy aging process, are all characterized by disruption of Ca2+ homeostasis and signaling. In this review we provide an overview of the main types of neuronal Ca2+ channels and their role in neuronal plasticity. We will also discuss the participation of Ca2+ signaling in neuronal aging and degeneration.